The Correlation Between Homesickness and Academic Achievement in Mathematics: Implications for Psychological Well-Being of Secondary School Students - Jennifer Adaobi Iloakasia (Journal of Education and Teacher Training Innovation, 2024)
This study examined the correlation between homesickness and academic achievement in mathematics among secondary school students, focusing on its implications for psychological well-being. A correlational research design was employed, involving a sample of 50 secondary school students from Awka South Local Government Area, Anambra State. Data were collected using Scale for Psychological Impact of Homesickness (SPIH) and the Mathematics Achievement Scale (MAS). Validity was ensured through expert consultations and Principal Component Analysis. Reliability was established with Kuder-Richardson formula 21 (K-R21) and Cronbach’s Alpha, yielding α = 0.89 for SPIH and α = 0.86 for MAS. Data were analyzed using SPSS, including non-parametric tests and normality assessments. The Spearman's rho correlation analysis revealed a significant, albeit weak, negative relationship between homesickness and academic achievement, indicating that higher levels of homesickness are associated with lower mathematics performance. Further analysis using the Mann-Whitney U test highlighted significant differences in homesickness levels and academic achievement between boarder and non-boarder students. These findings underscore the importance of addressing emotional challenges in educational settings. The study advocates for the implementation of comprehensive support systems, including counseling and resilience-building programs, to mitigate the impact of homesickness on academic performance. The results emphasize the need for schools to foster supportive environments that enhance students' psychological well-being and academic success. Future research should explore additional factors influencing this relationship to develop targeted interventions..